Implementasi End User Computing Satisfaction (EUCS) Dalam Pengukuran Kepuasan Pengguna Situs Web Badan Pertanahan Nasional - Diky Candra Muria Pratama; Kristoko Dwi Hartomo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
This study was conducted to determine the level of user satisfaction of the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) website so that website managers can get an overview of user satisfaction levels as well as future evaluation materials. Measurement of user satisfaction using the EUCS. The variables in this study were content, accuracy, format, ease of use, and timeliness. The sample in this study was collected from 168 respondents consisting of 3 Head of ATR/BPN, 17 BPN staff and 148 people who had accessed the ATR/BPN website. Collecting data using a closed questionnaire consisting of 13 questions for the five variables studied. From the data obtained, it is concluded that the overall level of user satisfaction is at an average value of 2.64 at level 3 (neutral), which means that according to the perception of general respondents, the website of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/ BPN) does not say satisfactory but also does not disappoint. The variables that are considered quite good are accuracy and ease of use, while the content, format, and timeliness are still being considered for further improvement and development. Keywords: Website, ATR/BPN, EUCS